Development of fabricated germanium-doped optical fibres for breast cancer electron beam dosimetry - Zakaria, Zabariah (2023)
In radiotherapy, electron beams are applied for superficial tumour treatment of less than 5 cm deep. Comparison between dose distribution in the patient and the distribution calculated by the treatment planning system (TPS) is essential to develop a novel radiation therapy. The response from the detector can be correlated to the dose received by the patients using the relationship between the doses at different places. An accurate absorbed dose measurement is easily performed with a well-functional detector. A new dosimeter, namely, Fabricated Germanium Doped Optical Fibres (FGDOFs) is developed by MCVD technique for electron beam dosimetry. Three objectives are addressed in this work: basic dosimetric characteristics, advanced dosimetric characteristics, and the clinical application of FGDOFs in breast cancer electron beam dosimetry. Clinically, investigations on breast dosimetry are conducted using the developed FGDOFs. Two types of FGDOFs, cylindrical fibre (CF) and flat fibre (FF) are doped with 2.3 and 6 mol% germanium. Electron beam energies from 6 MeV to 12 MeV, doses from 1 Gy to 5 Gy, dose rates from 100 to 600 cGy/min, focus to surface distance of 100 cm, and various field sizes are employed to analyse the FGDOFs dosimetric capabilities. Comparisons are made with commercial fibres, Lithium Fluoride (LiF) chips, GafchromicTM EBT3 films (EBT3 films), and ionisation chamber (IC). In terms of reproducibility, both CF and FF had a coefficient of variation of less than 5%. FGDOFs demonstrated a linear thermoluminescence (TL) response across the examined doses and energies. In terms of sensitivity, FF had a higher sensitivity by a factor of two compared to CF. The minimum detectable dose calculated has shown that FGDOFs is good at low-dose detection. Insignificant differences (p > 0.05) are found for FGDOFs with a percentage difference within ± 5% in terms of field size and dose-rate dependence. Conversely, FGDOFs showed energy dependency with a p ≤ 0.05 (95% confidence level). 23FF showed the lowest signal fading loss between 4.1 % and 5.9 % for a storage period of 13 days. Percentage depth dose of FGDOFs exposed to 9 MeV electron in a solid waterTM phantom is within 5% and agreeable to IC with no notable variations found in the build-up and fall-off regions. Higher signals produced by FF can be explained by their kinetic parameters such as maximum temperature (Tmax), activation energy (Ea), and peak integral (PI) based on the glow curve deconvolution. For FGDOFs, Tmax exhibits a consistent pattern from peak 1 to peak 5. FGDOFs also presented no discrepancies over the electron energies regarding the output factor. The combined uncertainties for 23CF, 23FF, 6CF, 6FF and LiF chips and EBT3 films were less than 3.5% with a coverage factor of k=1. For clinical applications in electron beam breast dosimetry, mean absorbed dose of FGDOFs showed an insignificant difference at p > 0.05 for skin dose, small and large tumour volume measurement when compared to the calculated dose obtained from the TPS. In conclusion, the developed FGDOFs, particularly FF, is found to be suitable for electron beam dosimetry.